Peningkatan Hasil Belajar Materi Diagram Gambar Matematika Melalui Media Audio-Visual Kelas II SD 02 Supriyadi Semarang (psnppg, 2025)
Low Mathematics learning outcomes in Picture Diagram material are a problem in class II of SD Supriyadi 02 Semarang. This research aims to improve learning outcomes by using Audio-Visual media. This type of research is classroom action research (PTK). The subjects of this research were class IIB students at SD Supriyadi 02 Semarang, totaling 29 students, consisting of 15 male students and 13 female students. This research was carried out in 3 action cycles, namely Pre-Cycle, Cycle I, Cycle II. Data collection techniques use observation, tests and documentation. Observation data was analyzed descriptively qualitatively. Test results were analyzed descriptively quantitatively. Based on the results of research, increasing classical completeness for class IIB SD Supriyadi 02 Semarang occurred in stages: Pre-Cycle, Cycle I, Cycle II. Before receiving treatment (Pre-Cycle), the classical completion rate only reached 38%. However, during Cycle I, the classical completion rate increased to 62%, and in Cycle II, it reached 90%. The indicator for success in classical completion is ≤75%. These results indicate a significant increase in classical completion during the study. From Pre-Cycle to Cycle II, students in class IIB showed good progress in understanding the Picture Diagram material. This indicates that the Audio-Visual media applied has been successful in increasing students' level of understanding to exceed the set success targets. Thus, this research succeeded in proving the effectiveness of Audio-Visual media in improving the classical mastery of class IIB students.
Keywords: Learning Outcomes; Mathematics; Audio-Visual Media